Self-assembly of a helical zinc-europium complex: speciation in aqueous solution and luminescence - Deiters, Emmanuel; Eliseeva, Svetlana V.; Bünzli, Jean-Claude G. (Frontiers in Chemistry, 2013)
Two new tridentate(NNO)-bidentate(NN) compartmental ligands, HL5 and HL6, are synthesized from pyridine and benzimidazole synthons. They react in aqueous solution under physiological conditions with ZnII, LnIII, or a mixture thereof, to yield complexes of different stoichiometries, 1:3, 2:2, 2:3, 1:1:3, the speciation of which is established by UV-visible titrations and ESI mass spectrometry. Photophysical studies of the EuIII-containing solutions in Tris-HCl 0.1 M (pH = 7.4) show that lanthanide luminescence arises from a unique N6O3 coordination site with pseudo D3 symmetry. Relevant parameters such as crystal field splitting, lifetime, radiative lifetime and intrinsic quantum yield perfectly match those reported for dinuclear 4f-4f helicates in which the EuIII ion has the same coordination environment.